(untitled) (Journal of Naval Architecture and Marine Engineering, 2017)
In this work, the effects of dimensionless parameters on the velocity field, thermal field and nanoparticle concentration have been analyzed. In this respect, the magnetohydrodynamic (MHD) boundary layer nanofluid flow along a moving wedge is considered. Therefore, a similarity solution has been derived like Falkner Skan solution and identified the point of inflexion. So the governing partial differential equations transform into ordinary differential equations by using the similarity transformation. These ordinary differential equations are numerically solved using fourth order RungeKutta method along with shooting technique. The present results have been shown graphically and in tabular form. From the graph, the results indicate that the velocity increases with increasing values of pressure gradient, magnetic induction and velocity ratio. The temperature decreases for velocity ratio, Brownian motion and Prandtl number but opposite result arises for increasing values of thermophoresis. The nanoparticle concentration decreases with an increase in pressure gradient, Brownian motion and Lewis number, but increases for thermophoresis. Besides, the solution of nanoparticle concentration exists in the case of Brownian motion is less than 0.2, thermophoresis is less than 0.14 and lewis number is greater than 1.0. Finally, for validity and accuracy the present results have been compared with previous work and found to be in good agreement.